Risk prediction method for power Internet of Things operation based on ensemble learning - Chao Hong; Xiaoyun Kuang; Yiwei Yang; Yixin Jiang; Yunan Zhang (EAI Endorsed Transactions on Energy Web)
INTRODUCTION: The power Internet of Things is an important strategic support for the State Grid Corporation of China to build an international leading energy internet enterprise. However, the operating environment of the power Internet of Things is complex and varied, which has serious implications for the safe operation of the power Internet of Things.